MIA-Directed 2‑Pyridione-Enabled Selective Ortho-C–H Arylation of Phenylalanine: A Mechanistic Study - Niu, Peng-Peng; Liu, Peng-Yu; Meng, Yue-Ning; Yu, Fang; He, Yu-Peng (Journal of organic chemistry, 2021)
The 2-methoxyiminoacyl-mediated arylation of substituted phenylalanines has been examined. Selective monoarylation at the ortho position was achieved using pyridone ligands which decelerate the arylation process. Density functional theory (DFT) study of a continuous C–H arylation process that included the first and second arylation stage was performed. The computational result shows that the introduction of a pyridone ligand obviously disfavors the second arylation stage, which directly contributes to the selectivity between the mono/diarylated products. Furthermore, results of the kinetic isotope effect and a control experiment are agreed with DFT study.